The correlation between structure and β-nucleation efficiency of Ba, Sr, Ca and Mg pimelates in isotactic polypropylene - Janevski, Aco; Bogoeva-Gaceva, Gordana; Stefov, Viktor; Najdoski, Metodija (Society of Chemists and Technologists of Macedonia, 2015)
The pimelates of the earth-alkaline elements and pimelic acid have been synthesized and studied. All prepared pimelates are crystallohydrates and Ba and Sr pimelates are isotypic. The obtained compounds have been characterized using infrared spectroscopy and X-ray diffraction, and it was found that, near and above the melting temperature of polypropylene, the pimelates of Ba and Sr are crystalline, whereas the ones of Ca and Mg are amorphous. The nucleation activity of these pimelates has been studied in the process of crystallization of polypropylene in non-isothermal conditions and followed by differential scanning calorimetry (at cooling rate Vc  = 1–20 K min–1). It was found that their nucleation activity, even at concentration of 0.1 %, differs considerably with regards to the cooling rate, and they induce different polymorphic composition of the polymer. The nucleation activity was mostly exhibited by Ca pimelate, and when it was used the content of the β crystalline phase (Uβ) in polypropylene ranged from 0.90 to 0.94, depending on the cooling  rate, compared to 0.18–0.35 when Mg pimelate was used. In the polymer crystallized by using Ba and Sr pimelate as nucleators, Uβ ranged from 0.47 to 0.77. Based on the theoretical concepts for nucleation activity of solid substrates, an attempt was made to correlate the structurаl features of the synthesized pimelates with their β-nucleation activity in the process of  nonisothermal crystallization of iPP.